The Spatial-Temporal Effects of Bacterial Growth Substrates on Antibiotic Resistance Gene Spread in the Biofilm - Shuzhen Liu; Bingwen Liu; Yin Zhu; Yong Qiu; Bing Li (MDPI AG, 2023)
Biofilm is considered as the hotspot of antibiotic resistance gene (ARG) dissemination. Bacterial growth substrates are important factors for biofilm formation, but its spatial-temporal effects on ARG spread in biofilm is still unclear. In this study, microfluidics combined with microscopic observation were used to reveal spatial-temporal effects of bacterial growth substrates on ARG transfer at real time. The initial horizontal gene transfer events were found to be independent of substrate levels. However, subsequent transfer processes varied greatly depending on the availability of growth substrates. The proportion of transconjugants was much higher (~12%) when observed in substrate-rich regions (under the channel) at 24 h, followed by an exponential decline, with the distance far from the channel. Furthermore, three-dimensional observation revealed that vertical gene transfer influenced by the concentrations of bacterial growth substrates was important for ARG spread in biofilm. The transfer frequency was 8.2 times higher in the high substrate concentration (50×) compared to low concentration (0.5×) in simulated sewage, underscoring the substantial impact of bacterial growth substrate variability on ARG dissemination. This study is helpful for in-depth understanding of ARG dissemination through biofilms and indicates that reducing pollutant emission is important for ARG control in the environment.